2009
DOI: 10.1007/s10029-009-0550-x
|View full text |Cite
|
Sign up to set email alerts
|

Single-incision laparoscopic trans-abdominal pre-peritoneal mesh hernia repair: a feasible approach

Abstract: This novel surgical technique is feasible and improves cosmetic outcome without additional risk. The advantage of such an approach above and beyond cosmesis remains to be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Rahman et al [13] reported the first case of SIL hernia (TAPP) repair. They used roticulating dissecting instruments and reported loss of tactile feedback using the instruments as compared to non-roticulating instruments.…”
Section: Discussionmentioning
confidence: 98%
“…Rahman et al [13] reported the first case of SIL hernia (TAPP) repair. They used roticulating dissecting instruments and reported loss of tactile feedback using the instruments as compared to non-roticulating instruments.…”
Section: Discussionmentioning
confidence: 98%
“…In 2010, Rahman and John [12] reported the first case of SILS hernia repair via the transabdominal preperitoneal approach (TAPP), improving cosmetic outcome with no additional risk.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the pursuit of minimally invasive surgery has given rise to the concept of natural orifice transluminal surgery (NOTES) and SILS. SILS for inguinal hernia repair has already been reported [8,9], but it has many problems in becoming a standard operation. The major problems of SILS are the clashing of instruments and the lack of triangular formation.…”
Section: Discussionmentioning
confidence: 99%